MEMBANGUN KARAKTER PESERTA DIDIK MELALUI KERJA SAMA KONSELING TERPADU - Nurbaiti yarso; Aloysius Mering; Indri Astuti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract: This study aimed at describing the form of cooperation on integrated counseling activities, knowing the efforts to build students’ character, describing the existing obstacles in character formation, and formatting integrated counseling cooperation with character building efforts, and even the obstacles in Public Elementary School 27 of Pontianak. The research method employed was qualitative research with data analysis techniques through triangulation on the source and method of the research, supported by descriptive percentages. Data collection was carried out by observation, documentation study, interviews, and questionnaires to the students. The results of the study are in the form of integrated counseling format that consist of the details of activities, goals, time, technique and counselors. Integrated counseling cooperation consists of components, namely principals, teachers, students, parents, and community leaders. Keywords: Character Building, Integrated Counseling